2016
DOI: 10.1016/j.biopsych.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Holocaust Exposure Induced Intergenerational Effects on FKBP5 Methylation

Abstract: This is the first demonstration of an association of preconception parental trauma with epigenetic alterations that is evident in both exposed parent and offspring, providing potential insight into how severe psychophysiological trauma can have intergenerational effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
359
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 569 publications
(428 citation statements)
references
References 56 publications
23
359
3
10
Order By: Relevance
“…The idea that intergenerational stress transmission is adaptive for offspring might explain findings where parents and offspring had opposite biological correlates of parental stress. For instance, Holocaust survivors exhibited inverse 11β-HSD2 activity and FKBP5 methylation compared with their offspring Bierer et al, 2014;Yehuda et al, 2015). If these original effects in parents reflect exposure to extreme stress, perhaps opposite marks or activity in offspring are intended to promote resilience in a similar context.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that intergenerational stress transmission is adaptive for offspring might explain findings where parents and offspring had opposite biological correlates of parental stress. For instance, Holocaust survivors exhibited inverse 11β-HSD2 activity and FKBP5 methylation compared with their offspring Bierer et al, 2014;Yehuda et al, 2015). If these original effects in parents reflect exposure to extreme stress, perhaps opposite marks or activity in offspring are intended to promote resilience in a similar context.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence shows that the offspring of male mice, who consumed a low protein diet during late childhood (from weaning until sexual maturity), have elevated expression of many genes in liver tissue and exhibit changes in cytosine methylation (Carone et al, 2010). Similarly, it has been shown that the offspring of Holocaust survivors had altered gene expression levels related to cortisol (Yehuda, 2015). Many studies argue that the most likely mechanism behind such phenomena are environmentally induced but heritable changes in the epigenome (Morgan et al, 1999, Rakyan et al, 2003, Ng et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Stress-and well-being-related methylation signals may be passed on from one generation to the next. The methylation of FKBP5, an important regulator of the glucocorticoid receptor, was recently found to be altered both in holocaust survivors and their adult offspring, pointing to a transgenerational effect of preconception parental trauma (Yehuda et al 2016). …”
Section: A Third Research Question Is About the Molecular Mechanisms mentioning
confidence: 99%